Leptospira Immunoglobulin-Like Protein B (LigB) Binds to Both the C-Terminal 23 Amino Acids of Fibrinogen αC Domain and Factor XIII: Insight into the Mechanism of LigB-Mediated Blockage of Fibrinogen α Chain Cross-Linking. - Ching-Lin Hsieh; Eric Chang; Andrew Tseng; Christopher Ptak; Li-Chen Wu; Chun-Li Su; Sean P McDonough; Yi-Pin Lin; Yung-Fu Chang (Public Library of Science (PLoS), 2016)
The coagulation system provides a primitive but effective defense against hemorrhage. Soluble fibrinogen (Fg) monomers, composed of α, β and γ chains, are recruited to provide structural support for the formation of a hemostatic plug. Fg binds to platelets and is processed into a cross-linked fibrin polymer by the enzymatic clotting factors, thrombin and Factor XIII (FXIII). The newly formed fibrin-platelet clot can act as barrier to protect against pathogens from entering the bloodstream. Further, injuries caused by bacterial infections can be confined to the initial wound site. Many pathogenic bacteria have Fg-binding adhesins that can circumvent the coagulation pathway and allow the bacteria to sidestep containment. Fg expression is upregulated during lung infection providing an attachment surface for bacteria with the ability to produce Fg-binding adhesins. Fg binding by leptospira might play a crucial factor in Leptospira-associated pulmonary hemorrhage, the main factor contributing to lethality in severe cases of leptospirosis. The 12th domain of Leptospira immunoglobulin-like protein B (LigB12), a leptospiral adhesin, interacts with the C-terminus of FgαC (FgαCC). In this study, the binding site for LigB12 was mapped to the final 23 amino acids at the C-terminal end of FgαCC (FgαCC8). The association of FgαCC8 with LigB12 (ELISA, KD = 0.76 μM; SPR, KD = 0.96 μM) was reduced by mutations of both charged residues (R608, R611 and H614 from FgαCC8; D1061 from LigB12) and hydrophobic residues (I613 from FgαCC8; F1054 and A1065 from LigB12). Additionally, LigB12 bound strongly to FXIII and also inhibited fibrin formation, suggesting that LigB can disrupt coagulation by suppressing FXIII activity. Here, the detailed binding mechanism of a leptospiral adhesin to a host hemostatic factor is characterized for the first time and should provide better insight into the pathogenesis of leptospirosis.